Heat-induced F0-fluorescence rise is not an indicator of severe tissue necrosis in thermotolerance assays of young and mature leaves of a tropical tree species, Calophyllum inophyllum - Winter, K; Garcia, M; Virgo, A (Photosynthetica, 2025)
In heating experiments with leaves, the temperature at which dark-level F0 chlorophyll a fluorescence begins to rise, Tcrit, is widely used as an indicator of photosystem II thermotolerance. However, little is known about how Tcrit correlates with irreversible leaf tissue damage. Young and mature leaves of the tropical tree species Calophyllum inophyllum were heated stepwise from 30 to 55°C, at 1°C min-1. Tcrit was 47°C in young leaves and 49°C in mature leaves. Contrary to the higher Tcrit in mature leaves, heating to 55°C elicited greater tissue damage in mature than in young leaves. Young and mature leaves heated to their respective Tcrit or Tcrit + 2°C exhibited no or little tissue necrosis after 14 d of post-culture. It is concluded that measurements of the temperature-dependent F0 fluorescence rise underestimate the thermal thresholds above which significant irreversible leaf damage occurs.
Keywords: listy rostlin; stromy; heat tolerance; chlorophyll a fluorescence; termotolerance; chlorofyl a; tropické klima; Chlorophyll; Trees; Chlorophyll A; nekróza; necrosis; Fluorescence; global warming; chlorofyl; Necrosis; Calophyllum; Plant Leaves; vysoká teplota; fluorescence; Thermotolerance; tropical trees; Tropical Climate; Hot Temperature